Predictors of fibrogenesis in children with JIA: a single-center pilot study - Olga Pavlova; Natalia Shevchenko; Sergey Pavlov; Tetiana Holovko; Liudmyla Bogmat (BMC, 2024)
Abstract Background Patients with rheumatological diseases are at high risk of developing irreversible fibrotic changes, both articular and extra-articular, as a result of tissue damage caused by the chronic phase of persistent inflammation. Thus, our purpose was to study early markers of fibrosis formation in children with juvenile idiopathic arthritis (JIA). Methods Seventy patients with juvenile idiopathic arthritis, namely, polyarthritis (64.29%) and oligoarthritis (35.71%) variant JIA (mean age 13.3 years, 64.29% girls, 35.71% boys), were included in this 4-year prospective study. Basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) levels were determined by ELISA kits. Results We evaluated bFGF (mean: 7478.21 pg/ml; min: 4171.56 pg/ml; max: 18,011.25 pg/ml) and VEGF (mean: 342.47 pg/ml; min: 23.68 pg/ml; max: 2158.91 pg/ml) levels in children with JIA. Children with JIA had a higher VEGF level when JIA onset occurred after 15 years of age and they had a high disease activity; additionally, a higher bFGF level was observed in children older than 14 years and in those with a JIA onset after 15 years of age, the oligoarticular variant, a moderate disease activity and regardless of MTX administration but more often when MTX was administered at a dosage from 10 to 12.5 mg/m2/week. Conclusions Laboratory screening of fibrosis formation predictors could help identify patients who may be at greater risk of adverse outcomes. Children with JIA had higher bFGF and VEGF levels when JIA onset occurred after 15 years of age, depending on disease activity.